Uma análise da qualidade de vida no trabalho dos servidores públicos de um município do Planalto Médio - Bugs, Robert (2022)
In the current context, Quality of Life at Work refers to a topic frequently addressed by organizations, given its growing importance with the constant changes in organizational environments. Within the scope of Public Administration, which has the duty to provide the best services and resources for the population, measuring the Quality of Life of its servers is beneficial, because through it it is possible to verify the degree of satisfaction of the server in the face of the organizational environment of the same, and what changes can be made to increase their satisfaction, reflecting on the quality of services provided by these servers. Through the present study, it was verified what is the perception on the part of public servants in the municipality of Nicolau Vergueiro, located in the northern region of the state of Rio Grande do Sul, about their Quality of Life at Work, using the Walton model to analyze their perception. The quantitative method was used to collect data from the servers, which is a questionnaire with closed questions created based on the Walton model and the research was carried out through the questionnaires. Positive results were found regarding the perception of Quality of Life at Work by the servers, demanding adjustments and improvements in the benefits provided by the management, in general the answers were given positively.